Systolic blood pressure reduction with stability as a new therapeutic goal in patients with intracerebral hemorrhage: results of the pooled analysis of ATACH 2 and INTERACT 2 trials - Qureshi, Adnan; Baskett, William; Martin, Renee H.; Lakhani, Pashmeen; Bhatti, Ibrahim A.; El Sabae, Hijrah; Al-Mufti, Fawaz; Gomes, Joao A.; Seifi, Ali; Rabinstein, Alejandro A.; Suarez, Jose I.; Steiner, Thorsten; et al. (Neurocritical care, 2025)
Background: The American Heart Association/American Stroke Association recommends achieving systolic blood pressure (SBP) therapeutic targets within 60 min of initiating treatment for intracerebral hemorrhage (ICH), emphasizing avoidance of “overshoot” correction and SBP fluctuations. We evaluated the prognostic value of “SBP reduction with stability,” a novel end point combining controlled blood pressure reduction and maintenance, using data from two large multinational clinical trials. Methods: We analyzed patients with ICH from Antihypertensive Treatment of Acute Cerebral Hemorrhage 2 and Intensive BP Reduction in Acute Cerebral Hemorrhage Trial 2 trials presenting with initial SBP 150–220 mm Hg. SBP reduction with stability was defined as achieving and maintaining SBP between 130 and 150 mm Hg within the first hour after randomization based on consecutive recordings. Outcomes included functional independence (modified Rankin scale 0–2) at 90 days and neurological deterioration within 24 h, adjusted for potential confounders. Results: Among 3,694 patients with ICH (2,781 patients from Intensive BP Reduction in Acute Cerebral Hemorrhage Trial 2 and 913 patients from Antihypertensive Treatment of Acute Cerebral Hemorrhage 2), 1,061 patients (28.7%) achieved SBP reduction with stability within 1 h. Patients had mean age 63.3 ± 12.9 years, baseline SBP 177.14 ± 18.28 mm Hg, and median hematoma volume of 10.78 mL (interquartile range 5.5–19.16). Achieving SBP reduction with stability significantly improved functional independence odds (odds ratio 1.38, 95% confidence interval 1.16–1.64) and reduced neurological deterioration odds (odds ratio 0.68, 95% confidence interval 0.53–0.88) after adjusting for initial SBP, Glasgow Coma Scale, age, sex, stroke history, hypertension, diabetes mellitus, study, ICH location, hematoma volume, and intraventricular hemorrhage presence. Conclusions: Only 30% of patients with mild‑to‑moderate ICH achieved SBP reduction with stability within the first hour. This achievement was associated with improved functional outcomes and reduced early neurological deterioration. These findings suggest that SBP reduction with stability represents a valuable therapeutic target for future clinical trials in ICH management.
Gesehen am 06.11.2025